Should there be lower taxes on patent income? - Fabian Gaessler; Bronwyn H. Hall; Dietmar Harhoff (Institute for Fiscal Studies (IFS), 2018)
A “patent box” is a term for the application of a lower corporate tax rate to the income derived from the ownership of patents. This tax subsidy instrument has been introduced in a number of countries since 2000. Using comprehensive data on patent filings at the European Patent Office, including information on ownership transfers pre- and post-grant, we investigate the impact of the introduction of a patent box on international patent transfers, on the choice of ownership location, and on invention in the relevant country. We find that the impact on transfers is small but present, especially when the tax instrument contains a development condition and for high value patents (those most likely to have generated income), but that invention itself is not affected. This calls into question whether the patent box is an effective instrument for encouraging innovation in a country, rather than simply facilitating the shifting of corporate income to low tax jurisdictions.
Keywords: H32; H34; K34; O34; 330; patent box; IP box; innovation tax; BEPS; EPO; invention incentive; patent ownership